Covid-19 and labor dynamics in the U.S. leisure and hospitality supersector - Akinjo, Iretiayo Rebecca (Kansas State University, 2023)
The COVID-19 pandemic has had a significant impact on the U.S. labor market. This study focuses on the labor dynamics in the Leisure and Hospitality Super-Sector. The Leisure and Hospitality Super-Sector comprises two sectors: Accommodation and Food Services; and Arts, Entertainment, and Recreation Sector. The research employed Bureau of Labor Statistics data to compare the changes in total separation, hires, and job opening rates between the Leisure and Hospitality Super-Sector and the Private Sector and between the Accommodation and Food Services and the Arts, Entertainment, and Recreation sectors resulting from the global COVID-19 pandemic. The study is important because while numerous studies have been conducted on the effects of the pandemic on the economy, there has not been a specific analysis of its effects on the Leisure and Hospitality Super-Sector, which has been indicated to encompass food services. Many governments, including the U.S. Government, responded to the pandemic with the immediate closure of the economy, which led to massive losses of the most jobs in the shortest time ever in recent history. The losses were most severe in the Leisure and Hospitality Super-Sector because of the precautionary policy of social distancing, which was difficult in businesses making up the sector. For example, the total separation rate in March 2020, when the global pandemic was declared, was 12.3% across the US economy, equivalent to about 15.75 million people. Total separation was about 5.3 million in the months prior and three months following March 2020. The study showed that the average total separation rate for the private sector was about 3.97% in the period prior to the pandemic and 4.67% during the pandemic. The difference of -0.70% was statistically significant (t = 5.87; p < 0.000). The average total separation rate for the leisure and hospitality sector was 6.18% and 8.35% in pre-pandemic and pandemic periods, the difference was statistically significant (t = 5.23; p < 0.000). The average total separation rate for the Accommodation and Food Services sector was 6.07% and 8.42%, respectively, in the pre-COVID and COVID periods (t = 5.76; p < 0.000). Similarly, the average total separation rate for the Arts, Entertainment, and Recreation sector was 6.83% prior to the pandemic and 7.99% after the pandemic (t = 2.70;p < 0.007). The research showed that the differences between the average total separation in the U.S. private sector and the Leisure and Hospitality Super-Sector were statistically significant in both the pre-COVID-19 and the COVID-19 periods. However, the difference in during the COVID-19 period was -3.68% (t = -3.45; p < 0.001) compared to -2.21 (t = 42.008; p < 0.000) in the pre-COVID-19 period. Similar observations were made for quits, hires, and job opening rates. Total separation, quits, and hire rates were defined as a function of unemployment rate, wage rate, median CPI, whether the economy was in a recession, and the impact of COVID for the whole economy, the Leisure and Hospitality Super-Sector, and its component sectors. The results showed that the regression coefficients for all the independent variables were statistically significant with the exception of the hourly wage rate. Specifically, the COVID-19 pandemic increased total separation in the private by 1.06% than without the pandemic. Comparatively, the COVID-19 coefficient for the Leisure and Hospitality Super-Sector was 3.39%, about three times that for the whole economy. This supports observations and other arguments that the COVID-19 pandemic had a much more serious impact on labor dynamics in the Leisure and Hospitality Super-Sector than it did on the general economy.
Keywords: COVID-19